2004
DOI: 10.1002/app.13667
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of polypropylene and poly(vinyl chloride) composites filled with plerospheres

Abstract: Plerospheres, defined here as superfine spherical particles (0.5-5 m) separated from fly ash (rather than as other solid spherical particles, as some have used the term), are separated from coal fly ash but are dramatically different from it. Plerospheres can be used as polymer fillers to improve the properties of composites. With plerospheres used as fillers for polypropylene (PP) and unplasticized poly(vinyl chloride) (UPVC), the effects of the filler content, the particle sizes of the plerospheres, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The FACs are mainly composed of SiO 2 and Al 2 O 3 , and can generate many hydroxyl groups on the surfaces under the action of air [32]. The coupling process can be accomplished via the chemical reaction between the alkoxy groups of silane molecules and surface hydroxyl groups of FACs, whereas other functional groups of silane, such as ethylene, amine, epoxy, thiohydroxy, etc., are remained.…”
Section: Synthesis Processmentioning
confidence: 99%
“…The FACs are mainly composed of SiO 2 and Al 2 O 3 , and can generate many hydroxyl groups on the surfaces under the action of air [32]. The coupling process can be accomplished via the chemical reaction between the alkoxy groups of silane molecules and surface hydroxyl groups of FACs, whereas other functional groups of silane, such as ethylene, amine, epoxy, thiohydroxy, etc., are remained.…”
Section: Synthesis Processmentioning
confidence: 99%
“…Plerospheres are defined as superfine spherical particles (0.5 -5 microns) separated from FA. It was observed that lower torque was required with silane-coated plerospheres than uncoated plerospheres [23].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of utilizing fly ash as filler in different polymeric materials is growing exponentially [1][2][3][4][5][6][7][8][9][10][11]. Surface treatment is a principal method applied to change the wetting behaviour of mineral or inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%